Hair Interpolation for Portrait Morphing. (25th November 2013) - Weng, Yanlin; Wang, Lvdi; Li, Xiao; Chai, Menglei; Zhou, Kun
Abstract: In this paper we study the problem of hair interpolation: given two 3D hair models, we want to generate a sequence of intermediate hair models that transform from one input to another both smoothly and aesthetically pleasing. We propose an automatic method that efficiently calculates a many‐to‐many strand correspondence between two or more given hair models, taking into account the multi‐scale clustering structure of hair. Experiments demonstrate that hair interpolation can be used for producing more vivid portrait morphing effects and enabling a novel example‐based hair styling methodology, where a user can interactively create new hairstyles by continuously exploring a "style space" spanning multiple input hair models.